1997
DOI: 10.1046/j.1365-2141.1997.4813284.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Bcl‐2/Bax protein levels in platelets form part of an ionomycin‐induced process that resembles apoptosis

Abstract: Platelets are physiologically anucleated cells, derived from megakaryocytes, that undergo vesiculation and transformation into small particles when they are stimulated in vitro by ionomycin and other agents. Electron microscopy images suggest a similarity to apoptosis in cells with nuclei, which ends with cell disintegration and formation of apoptotic bodies. By PCR, we have demonstrated mRNA expression of bcl-2, bax, and p53 in highly purified non-stimulated platelets. A side-scatter shift and a decrease in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
87
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 46 publications
13
87
0
1
Order By: Relevance
“…However, the caspase inhibitor z-VAD-fmk does not prevent phosphatidylserine exposure in activated platelets. 9,22,34 In addition, Wolf et al 22 demonstrated that calpain was able to process procaspase-3 and procaspase-9 at specific cleavage sites without generating the active caspase subunits and proposed that calpains, but not caspases, were responsible for apoptosis-like events during platelet activation. 42,43 The role of caspases in platelet Flow cytometry analysis of death receptors and ligands.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…However, the caspase inhibitor z-VAD-fmk does not prevent phosphatidylserine exposure in activated platelets. 9,22,34 In addition, Wolf et al 22 demonstrated that calpain was able to process procaspase-3 and procaspase-9 at specific cleavage sites without generating the active caspase subunits and proposed that calpains, but not caspases, were responsible for apoptosis-like events during platelet activation. 42,43 The role of caspases in platelet Flow cytometry analysis of death receptors and ligands.…”
Section: Figurementioning
confidence: 99%
“…9,26,34 Some of these Bcl-2-related proteins are pro-apoptotic proteins, which are present in healthy cells in a dormant form and behave as stress sensors by monitoring the integrity of vital metabolic processes. 33 One of them is the BH3 domain-only protein Bim 44 that is expressed in many hematopoietic cell types and is sequestered to cytoskeletal structures of healthy cells via association with dynein light chain LC8.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…3,[11][12][13] Several studies have demonstrated that the Bcl-2 family proteins (i.e., Bax, Bak, Bcl-X L , and Bcl-2) are also expressed in platelets. 11,12,14,15 The Bcl-2 family of proteins is the key regulators of mitochondria-dependent apoptosis in nucleated cells and consists of both antiapoptotic (Bcl-X L , Bcl-2, Bcl-w, A1, Mcl-1) 16 and proapoptotic (Bak, Bax, Bid, Bim, Bad, Bik, Bmf, Noxa, Puma) 17 members.…”
mentioning
confidence: 99%